2020
DOI: 10.18502/ijrm.v18i12.8024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha-lipoic acid supplementation on the lipid profile and lipid ratios in women with gestational diabetes mellitus: A clinical trial study

Abstract: Background: Evidence suggests that Oxidative stress has been shown to plays an important role in gestational diabetes mellitus (GDM) etiology. On the other hand, women with GDM are at an increased risk for complications such as endothelial dysfunction and cardiovascular diseases. Objective: To investigate the effects of alpha-lipoic acid (ALA) on the maternal circulating values of lipid profile and lipid ratios in women with GDM. Materials and Methods: Sixty women with GDM were participated in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
3
0
1
Order By: Relevance
“…Overall, these data represent the first evidence that Myo is able to improve endothelial stress/damage in vascular cells by modulating inflammation and oxidative stress related to diabetes. These effects are comparable to the protective vascular action of LA, a molecule with well-known antioxidant effects that has demonstrated safety as well as beneficial effects on glycemia and liver enzymes as well as on lipid profiles and on adiponectin/leptin ratios in women affected by either GDM or polycystic ovary syndrome [ 8 , 27 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…Overall, these data represent the first evidence that Myo is able to improve endothelial stress/damage in vascular cells by modulating inflammation and oxidative stress related to diabetes. These effects are comparable to the protective vascular action of LA, a molecule with well-known antioxidant effects that has demonstrated safety as well as beneficial effects on glycemia and liver enzymes as well as on lipid profiles and on adiponectin/leptin ratios in women affected by either GDM or polycystic ovary syndrome [ 8 , 27 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 96%
“…Finally, a very- or low-GRADE quality score for most outcomes (supplements: FPG and PPG; diet: FPG, PPG, and HbA1c; exercise: PPG, HbA1c, and HOMA-IR) due to limitations in the design of included studies (e.g., allocation concealment, lack of blinding of either outcome assessors or participants, reporting of adherence to the intervention) could explain the lack of difference between intervention and control. The strengths of this review should be noted, as far as we know, this is the first SRMA that shows the benefits of supplement-, dietary-, and exercise-based interventions on measures of glycemic control in GDM, including more recent studies not included by the preceding SRMAs [ 26 , 28 , 31 , 42 , 51 ]. Overall this SRMA included a large number of participants with varied backgrounds and examines the effectiveness of lifestyle interventions on maternal glycemic control, ultimately reducing the risk of adverse perinatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clinical trial study which reported the curative effect of ALA in GDM pregnancies. In this study, women with GDM showed a significant decrease in the maternal circulating values of triglyceride-glucose index, triglyceride (TG), TG/high-density lipoprotein cholesterol, atherogenic index of plasma, and thiobarbituric acid-reactive substances in the ALA group compared to the placebo group at the end of the intervention [ 93 ].…”
Section: Antioxidantsmentioning
confidence: 99%